PARITY AND HUSBAND'S SUPPORT IN THE UTILIZATION OF ANTENATAL CARE SERVICES IN NUSA TENGGARA TIMUR PROVINCE - Erny Widya Yanti, Ni Made; Seri Ani, Luh; Lubis, Dinar (Majalah Kesehatan, 2026)
Low utilization of antenatal care (ANC) services contributes to rising maternal mortality rates. While low utilization of antenatal care (ANC) services contributes to rising maternal mortality rates, the specific factors influencing ANC uptake in East Nusa Tenggara (NTT) Province remain varied. This study aims to identify factors associated with ANC utilization in East Nusa Tenggara (NTT) Province. A cross-sectional study was conducted using secondary data from the 2017 Indonesia Demographic and Health Survey (IDHS). A total of 790 women of reproductive age who had given birth within five years prior to the survey were selected using stratified sampling. Data on ANC utilization, socio-demographic factors (including age, education, residence, employment, marital status, and wealth quintile), obstetric history, and access/support variables were analyzed using logistic regression. ANC utilization was defined as completing at least four visits during pregnancy. The results showed that 74.7% of women completed the full ANC visits. Parity and husband’s support were significantly associated with ANC utilization (p < 0.05). Conversely, age, education, residence, employment, marital status, pregnancy status, health insurance, wealth quintile, transportation ownership, media exposure and need factors showed no significant association (p > 0.05). This study underscores the critical roles of parity and husband’s support in improving ANC uptake. Thus, increasing access to targeted information is recommended to enhance husband’s involvement and support in maternal health services.